1986
DOI: 10.1093/ajcp/85.4.402
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of Granulosa Cell Tumor of the Ovary

Abstract: Granulosa cell tumor of the ovary may create a diagnostic challenge in cytologic preparations. Our experience with needle aspiration material, ascitic fluid, and peritoneal washings indicates that in fluids, despite some similarity between the tumor cells and reactive mesothelial cells, a correct diagnosis can be achieved by careful examination. The paucity of the cytoplasm and an intense indentation of nuclear membrane are the most helpful features in distinguishing the granulosa cells from mesothelial cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…[ fig.3] In cases of granulosa cell tumor cytology showed clusters of medium-sized cells with round to ovoid monomorphic nuclei and finely granular chromatin. Nuclear grooves were present in some but not all the cells, similar to Ehya et al 12 Of the 4 cases reported as serous cystadenoma on FNAC, 2 of them proved to be borderline serous cystadenoma, 1 serous cystadenocarcinoma and 1 was diagnosed as granulose cell tumor on histology. 1 case was diagnosed as mucinous cystadenoma on cytology but labeled as mucinous cystadenocarcinoma on histology.…”
Section: Discussionsupporting
confidence: 76%
“…[ fig.3] In cases of granulosa cell tumor cytology showed clusters of medium-sized cells with round to ovoid monomorphic nuclei and finely granular chromatin. Nuclear grooves were present in some but not all the cells, similar to Ehya et al 12 Of the 4 cases reported as serous cystadenoma on FNAC, 2 of them proved to be borderline serous cystadenoma, 1 serous cystadenocarcinoma and 1 was diagnosed as granulose cell tumor on histology. 1 case was diagnosed as mucinous cystadenoma on cytology but labeled as mucinous cystadenocarcinoma on histology.…”
Section: Discussionsupporting
confidence: 76%
“…8,9,13,15,17,18 Even fewer reports describe the cytologic features of JGCT, and the majority of these cases are single cases. Our series consisted of 7 cases of ovarian GCT, including 1 JGCT and 6 AGCTs.…”
Section: Discussionmentioning
confidence: 99%
“…These cytologic features were selected because of their previous (and repeated) description in the cytology literature. [8][9][10][11][12][13][14][15][16][17][18][19] In addition, each case was examined for single cell necrosis, increased mitoses (normal and abnormal) and features of cellular atypia. For the purpose of the study, cellular atypia was defined as tumor cells showing; pleomorphism, hyperchromasia, prominent nucleoli (2-3 μm or larger) and/or increased mitoses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells are fairly uniform, with round or oval, often indented nuclei, sometimes with distinct grooves. [9][10][11][12] Nuclear grooves have been reported to be of value in the diagnosis of granulosa cell tumors 10 but have been observed in follicular cysts and maturing follicles. 6 Our case supports that observation.…”
Section: Discussionmentioning
confidence: 99%